2010
DOI: 10.1016/j.compscitech.2010.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the thermal conductivity of composite materials with imperfect interfaces

Abstract: This paper compares the predicted values of the thermal conductivity of a composite made using the equivalent inclusion method (EIM) and the finite element method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Numerical modeling based on finite element analyses has been widely used to predict the effective properties of composites, including the mechanical, thermal, electrical, piezoelectric, thermoelectric properties (Pan et al, 2008;Wang et al, 2011;Miled et al, 2013;Lu et al, 2014;Doghri et al, 2016;Lee et al, 2018aLee et al, , 2019. However, to obtain statistically meaningful results, finite element analyses require multiple evaluations of large simulation cells involving a large number of fillers, thus necessitating a much fine mesh near the boundary to serve as representative volumes and leading to the requirement of computationally expensive and time-consuming calculations (Xu and Yagi, 2004;Marcos-Gomez et al, 2010;Lee et al, 2018aLee et al, , 2019. Such extensive numerical calculations are feasible for predictions of the effective properties of systems in the linear response regime.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical modeling based on finite element analyses has been widely used to predict the effective properties of composites, including the mechanical, thermal, electrical, piezoelectric, thermoelectric properties (Pan et al, 2008;Wang et al, 2011;Miled et al, 2013;Lu et al, 2014;Doghri et al, 2016;Lee et al, 2018aLee et al, , 2019. However, to obtain statistically meaningful results, finite element analyses require multiple evaluations of large simulation cells involving a large number of fillers, thus necessitating a much fine mesh near the boundary to serve as representative volumes and leading to the requirement of computationally expensive and time-consuming calculations (Xu and Yagi, 2004;Marcos-Gomez et al, 2010;Lee et al, 2018aLee et al, , 2019. Such extensive numerical calculations are feasible for predictions of the effective properties of systems in the linear response regime.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the orientation of carbon nanofibers in a copper matrix leads to anisotropic thermal conductivity [25]. In such perspective, the present work aims at investigating the anisotropic thermal conductivity behaviour of ceramic metal composites processed from freeze casted ceramic performs.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical modeling based on finite element analyses has been widely used to predict the effective properties of composites, including the mechanical, thermal, electrical, piezoelectric, thermoelectric properties (Pan et al, 2008;Wang et al, 2011;Miled et al, 2013;Lu et al, 2014;Doghri et al, 2016;Lee et al, 2018a;Lee et al, 2018b). However, to obtain statistically meaningful results, finite element analyses require multiple evaluations of large simulation cells involving a large number of fillers, thus necessitating a much fine mesh near the boundary to serve as representative volumes and leading to the requirement of computationally expensive and time-consuming calculations (Xu and Yagi, 2004;Marcos-Gomez et al, 2010;Lee et al, 2018a;Lee et al, 2018b). Such extensive numerical calculations are feasible for predictions of the effective properties of systems in the linear response regime.…”
Section: Introductionmentioning
confidence: 99%